How traditional cultural load affects tourists' purchasing intention of tourist souvenirs. - Qingxi Huang; Dajun Yang; Yixin Xie; Fuqiang Tan; Tingyue Kuang (PLoS ONE)
Based on the previous studies on the impact of traditional culture on tourists' purchasing intentions, this study aims to further explore the mechanism and boundary conditions regarding the traditional cultural load in tourist souvenir packaging. Through seven simulated experiments (N = 3203), the impact of different degrees of traditional cultural load on tourists' purchasing intentions has been examined, with value perception, cultural identity, and purchase purpose, advancing the research in the field of traditional culture and tourism marketing. The findings provide insights for managers in the industry of tourism and souvenir marketing for their package design.